A bertrand game-based approach to hotel yield management strategies - Watada, J. (IGI Global, 2016)
This chapter examines hotel yield management from a game perspective using a duopoly situation of two hotels. The hotel yield management determines strategies by considering the number of available rooms in the Bertrand situation. Each hotel does not know the strategies adopted by a competitive hotel. We derive the strategy that realizes a maximum profit under a given situation and constraints. Furthermore, we validate the game-based strategy developed for hotel yield management. In the real world, a business manager adopts an optimum strategy of yield management to gain profits in the current conditions; after the initial strategy is chosen, however, managers continuously weigh new strategies and investments. Therefore, we import the method of real option. Such maneuvers and investments are required to build new strategies amidst competition in the industry. Â© 2017, IGI Global.